Nieklienci i antyklienci banków. W kręgu rozważań o niechęciach właścicieli firm mikro i małych wobec banków - Sołoma, Andrzej (Nonclients and Anticlients of Banks. Deliberations on Reluctance of Micro and Small Business Owners Towards Banks, 2007)
The article presents some of the findings from research concerning bank lending to 342 micro and small firms operating in Warmińsko-Mazurskie voivodeship. Many of small business owners can be described as anticustomers of banks. In spite of lending propositions of many financial institutions, some owners are not willing to sign a loan agreement. Number of small business firms taking a bank loans in 2005 was only slightly higher than three years ago.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 400-407